Understanding of the immunological heterogeneity of canine mammary carcinomas to provide immunophenotypic features of circulating leukocytes as clinically relevant prognostic biomarkers - Lima, Alessandra Estrela da Silva (2012)
Acesso restrito: texto completo. p. 751-763